Proud to belong: the impact of ethics training on police officers - Harris, D; Borcan, O; Serra, D; Telli, H; Schettini, B; Dercon, S (University of Oxford, 2022)
We investigate whether ethics and integrity training can improve values, attitudes and behavior of police officers. We conducted a field experiment in Ghana, where we randomly selected traffic police officers to participate in a training program informed by theoretical work on the role of identity and motivation in organizations. The training was designed to re-activate intrinsic motivations to serve the public, and to create a new shared identity of “Agent of Change,” aimed at inducing a collective shift in attitudes and behaviors. Data generated by a survey and an incentivized cheating game conducted 20 months later, show that the program positively affected officers’ values and beliefs regarding on-the-job unethical behavior and improved their attitudes toward citizens. Moreover, the program significantly lowered officers’ propensity to behave unethically, as measured by their willingness to cheat in the incentivized game.